PSVII-6 Effects of heat stress on proteolysis in dairy cattle skeletal muscle - Roths, Melissa S (J Anim Sci, 2020)
Heat stress (HS) occurs when internal body temperatures are elevated above a thermoneutral zone in response to extreme environmental temperatures. In the U.S. dairy industry, HS results in economic loss due to decreased feed intake, milk quality, and milk yield. Previous work has demonstrated increased plasma urea nitrogen in heat stressed dairy cattle which is thought to originate from increased skeletal muscle proteolysis, however this has not been empirically established. The objective of this investigation was to determine the extent to which HS promotes proteolysis in skeletal muscle of dairy cattle. We hypothesized HS would increase activation of the calpain and proteasome systems in skeletal muscle. To test this hypothesis, following a 3-d acclimation period in individual box stalls, all lactating dairy cows were held under thermoneutral (TN) conditions for 4-d for collection of baseline measures and then exposed to TN or HS conditions for 7-d followed by a biopsy of semitendinosus (n=8/group). To induce HS, cattle were fitted with electric heating blankets, which they wore for the duration of the heating period. This approach increased rectal temperature 1.1°C (P< 0.05), respiratory rate by 33 bpm (P< 0.05), plasma urea nitrogen by 19% (P=0.08) and milk urea nitrogen by 26% (P< 0.05), and decreased dry matter intake by 32% (P< 0.05) and milk production by 26% (P< 0.05) confirming HS. Contrary to our expectations, we discovered that calpain I and II abundance and activation, and calpain activity were similar between groups. Likewise, protein expression of E3 ligases, MafBx and Murf1, were similar between groups as was total ubiquitinated proteins and proteasome activity. Collectively, and counter to our hypothesis, these results suggest skeletal muscle proteolysis is not increased following 7-d of HS. These data question the presumed dogma that increased blood urea nitrogen is due to elevated proteolysis in skeletal muscle.